Biaryl sulfonamides as cisoid azosteres for photopharmacology. Issue 34 (26th March 2021) - Kobauri, Piermichele; Szymanski, Wiktor; Cao, Fangyuan; Thallmair, Sebastian; Marrink, Siewert J.; Witte, Martin D.; Dekker, Frank J.; Feringa, Ben L.
Abstract : Biaryl sulfonamides are excellent candidates for the azologization approach that yields photoswitchable drugs more active in their metastable cis state, compared to the stable trans state. Abstract : Biaryl sulfonamides are excellent candidates for the azologization approach that yields photoswitchable drugs more active in their metastable cis state, compared to the stable trans state. Here we present the scope and limitations of this strategy for rational design in photopharmacology.